Current problems of vocational education in the Federal Republic of Germany - Schmidt, Hermann [Verfasser] (The National Center for Research in Vocational Education, The Ohio State University, 1979)
"Dr. Schmidt‘s seminar, entitled „Current Problems of Vocational Education in the Federal Republic of Germany“, proved timely and insightful. In his lecture, Dr. Schmidt outlined the history of vocational education in the Federal Republic and explained the measures the German government has taken to insure adequate vocational training for German youth. He also emphasized the fact that the US and Germany have much more in common and much to share in the area of vocational training." (Excerpt, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 2.3 Berufsbildungspolitik; I 2.1 Deutschland; 370; Berufsbildung; Berufsbildungspolitik; Geschichte; Historische Entwicklung; Bundesrepublik Deutschland; 1960-1979